Association of mitochondrial copy number variation and T16189C polymorphism with colorectal cancer in North Indian population - Bhupender Kumar; Zafar Iqbal Bhat; Savita Bansal; Sunil Saini; Afreen Naseem; Khushnuma Wahabi; Archana Burman; Geeta Trilok Kumar; Sundeep Singh Saluja; M Moshahid Alam Rizvi (Tumor Biology, 2017)
Globally, colorectal cancer is the third most common type of cancer. Genetic instability leading to cancer development is one of the major causes for development of cancer. Alterations in mitochondrial genome, that is, mutations, single-nucleotide polymorphisms, and copy number variations are known to contribute in cancer development. The aim of our study was to investigate association of mitochondrial T16189C polymorphism and copy number variation with colorectal cancer in North Indian population. DNA isolated from peripheral blood of 126 colorectal cancer patients and 114 healthy North Indian subjects was analyzed for T16189C polymorphism and half of them for mitochondrial copy number variation. Genotyping was done using polymerase chain reaction–restriction fragment length polymorphism, and copy number variation was estimated using real-time polymerase chain reaction, numbers of mitochondrial copies and found to be significantly higher in colorectal cancer patients than healthy controls (88 (58–154), p = 0.001). In the regression analysis, increased mitochondrial copy number variation was associated with risk of colorectal cancer (odds ratio = 2.885, 95% confidence interval = 1.3–6.358). However, T16189C polymorphism was found to be significantly associated with the risk of rectal cancer (odds ratio = 5.213, p = 0.001) and non-significantly with colon cancer (odds ratio = 0.867, p = 0.791). Also, false-positive report probability analysis was done to validate the significant findings. Our results here indicate that mitochondrial copy number variation may be playing an important role in the development of colorectal cancer, and detection of mitochondrial copy number variation can be used as a biomarker for predicting the risk of colorectal cancer in North Indian subjects.